2020
DOI: 10.5741/gems.56.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Natural Laboratory-Grown Diamond Using Time-Gated Luminescence Imaging

Abstract: A technique that expands on the surface luminescence imaging used in the DiamondView instrument has been developed at De Beers Group Technology, Maidenhead, UK. This provides an additional level of imaging information by way of separating prompt and delayed surface luminescence. The technique has the added benefit of quickly and easily distinguishing colorless or near-colorless natural diamond from laboratory-grown diamond. It can be applied when the identification of natural diamond is required in the study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…[ 15,16 ] However, previous studies have demonstrated that the above bandgap excitation of the blue dislocation luminescence in natural diamonds during the prompt timeframe is not observed from the blue luminescence observed during the delayed timeframe. [ 4 ] The blue dislocation‐like prompt luminescence observed in CVD diamond is also not observed in the delayed luminescence. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15,16 ] However, previous studies have demonstrated that the above bandgap excitation of the blue dislocation luminescence in natural diamonds during the prompt timeframe is not observed from the blue luminescence observed during the delayed timeframe. [ 4 ] The blue dislocation‐like prompt luminescence observed in CVD diamond is also not observed in the delayed luminescence. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon forms the basis for the De Beers SYNTHdetect instrument, which is used to distinguish between natural and synthetic diamonds. [ 4 ] Recently, we have observed a delayed spectrally broad blue luminescence centered at 465 nm in a synthetic diamond grown by chemical vapor deposition (CVD) when measured at temperatures below 190 K. This previously undocumented blue emission, not yet fully understood, serves as a reference point in our exploration of synthetic diamonds. We intend to introduce this novel feature to the scientific community, marking its initial identification as a phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Such CVD diamonds are rarely grown for gem purposes due to cost. Instead, deep-UV fluorescence images of as-grown colorless, near-colorless or brown CVD diamonds usually show orange, red or pink bulk fluorescence due to NV center emission (Wang et al 2003(Wang et al , 2005b(Wang et al , 2007bMartineau et al 2004;Wassell et al 2018;McGuinness et al 2020). They may also weakly phosphoresce orange or blue (Wang et al 2007b;McGuinness et al 2020).…”
Section: Strain Birefringence Patternsmentioning
confidence: 99%
“…Instead, deep-UV fluorescence images of as-grown colorless, near-colorless or brown CVD diamonds usually show orange, red or pink bulk fluorescence due to NV center emission (Wang et al 2003(Wang et al , 2005b(Wang et al , 2007bMartineau et al 2004;Wassell et al 2018;McGuinness et al 2020). They may also weakly phosphoresce orange or blue (Wang et al 2007b;McGuinness et al 2020). HPHT annealing for decolorization introduces H3 (N 2 V 0 ), N3 (N 3 V 0 ), and a series of unidentified emission peaks and bands between 430 and 500 nm (Wang et al 2012 ;Wassell et al 2018;McGuinness et al 2020).…”
Section: Strain Birefringence Patternsmentioning
confidence: 99%
See 1 more Smart Citation